Toward a Framework of Integrating Ability: Conceptualization and Design of an Integrated Physics and Mathematics Test - Haydée De Loof; Stijn Ceuppens; Jolien De Meester; Leen Goovaerts; Lieve Thibaut; Mieke De Cock; Wim Dehaene; Fien Depaepe; Heidi Knipprath; Jelle Boeve-de Pauw; Peter Van Petegem (Education Sciences, 2023)
The awareness that many problems in our society are interdisciplinary in nature and require the integration of multiple STEM (Science, Technology, Engineering, Mathematics) concepts to solve them has given rise to a new instructional approach, called “integrated STEM education”. Integrated STEM education aims to remove the barriers from the STEM fields and has the potential to increase students’ interest and motivation for learning, as well as to lead to improved achievement. It is important to assess the effectiveness of educational STEM initiatives in terms of students’ integrating ability, but to date, no such instruments are available. This study provides a definition of “integrating ability” and establishes a framework for understanding its components. Based on this definition and framework, a multiple-choice instrument for testing integrated physics and mathematics in the ninth grade (IPM9) was developed and validated. The definition and framework for integrating ability and the construction guidelines for an integrated test, can be used by researchers to assess students’ ability to integrate STEM subjects.